THE FABC AND ECOLOGICAL ISSUES - Tirimanna, Vimal (Asian Horizons, 2012)
Although the documents of the Federation of Asian Bishops’ Conferences (FABC) had been consistent and insistent on ecological issues all along, there has not yet been a separate document of the FABC exclusively dedicated to these issues.1 In the wake of the everunfolding ecological relevance for today’s world, recently there was a special seminar sponsored by the FABC on Climate Change in Bangkok from 19th to 20th October 2011,2 during which the Secretary General of the FABC Arcbbishop Orlando Quevedo assured the delegates that the emerging mega-trend of ecology will certainly be a topic at the forthcoming 10th Plenary Assembly of the FABC which is due in November 2012 in Vietnam. Of late, the FABC has also decided to institute a special FABC Desk for ecological issues.